PETROGENESIS AND ALTERATION OF TUFFS ASSOCIATED WITH CONTINENTAL FLOOD BASALTS FROM PUTORANA, NORTHERN SIBERIA - Büchl A.; Gier S. (My University, 2003)
In the Putorana region of the Siberian continental flood basalt province, tuffs form thin layers or small bodies between single basaltic lava flows. Based on our fieldwork, these ash fall deposits have relatively small volumes ([less-than-or-equal]100 000 m3) compared with the associated basaltic flows and the tuffs of the adjacent Noril'sk region in the north. Six tuff units with different degrees and modes of alteration were analysed by XRD, SEM and XRF in order to determine mineralogical and chemical changes which occurred during progressive alteration. Pyroxene compositions and immobile element ratios suggest that the tuffs were derived from a basaltic lava like the flood basalts. Post-eruptive, low-temperature alteration processes have significantly changed the primary composition of the tuffs. Therefore the different tuffs have variable petrography, mineralogy and geochemistry (MgO 5.269.1 wt % and TiO2 0.6sediment interaction, and one sample was deposited in a subaqueous, possibly lacustrine environment. These results indicate that the conditions during alteration varied despite the close spatial relationship of the tuffs and that a generalization about the alteration processes cannot be made in the Putorana region. The analyses of the clay minerals show alteration of chlorite to vermiculite. Interestingly, corrensite (a regularly stacked, 50/50 mixed layered clay mineral composed of chlorite and vermiculite) is still preserved in two samples. This indicates different alteration stages in the different tuff outcrops. The state of alteration deduced from immobile element ratios, plagioclase compositions and mineral assemblages shows contradictory results. This suggests that the state of alteration is best deduced from clay minerals, as one can follow this process step by step.